Pemilihan Motor Listrik Sebagai Penggerak Utama dan Propeller Sebagai Alat Gerak Pada Sistem Propulsi Pesawat Flying Wing PX - Endah Yuniarti; Tri Susilo; Albi Nuari Hastono (Jurnal Teknologi Kedirgantaraan, 2016)
Election electric motor as main motor engine and propeller as mechanical device of propulsion system Flying Wing PX aircraft has been done. The types of investigated electrics motor are EMAX BL 2382/05, NTM Pprop Drive Series 42-58 and Turnigy 3648. The propellers that have been tested are 12x8, 13x8, 14x7 and 15x7 dimension propeller. Parameters that have been investigated are power, velocity of motor, velocity of propeller and thrust. Effect of parameters on aircraft performance has been analyzed. Power as result from motor currents multiplied 11,1 volt baterai voltage. Velocities of motors as result from value of KV that technical term for explain how many motor rotation each second in 1 volt applied voltage. Propeller velocities were measured by Tachometer device. Air flow velocities were measured by Digital Anemometer Air Flow Meter. Furthermore, it’s used for thrust calculation. The result showed that the highest power and motor velocities obtained by EMAX BL 2382/05 is 888 watts and 8935 rpm. With the 888 watts as highest power, the aircraft is able to do sport performance. The propeller velocities which is appropriate with motor velocities maximum limit is 13x8 and 14x7 dimensions, but the highest thrust obtained by 14x7 dimensions. Thus, EMAX BL 2382/05 electric motor and 14x7 dimension propeller can used at Flying Wing PX aircraft in order to aircraft performance is maximal.